Ecos da presença feminina na Igreja Presbiteriana de Cuiabá (1920 a 1934) - Araujo, Adilson Maciel de (2024)
This dissertation approaches the presence of Presbyterian women in Cuiabá in the first decades of the implementation of Presbyterianism in Mato Grosso. In the transition from the 19th to the 20th century and in the first decades of this, women faced social, cultural and religious barriers that limited their participation in public spaces. That way, it was not different in the religious environment. However, they were able to participate in activities such as biblical teaching and evangelization. During this period, Protestantism arrived in Cuiabá to take roots. The first Protestant family responsible for the origin of Presbyterianism appears in documentary sources at the end of the 19th century. Mrs. Melo and Mrs. Dias (D. Josefa), in addition to being the mothers of seven children, they mark the Protestant presence in Cuiabá. Added to them, there are the wives of American missionaries with their undeniable contributions. The presence of Presbyterian woman, in the first decades of the implementation of Protestantism in Cuiabá, was flagged by important advances and achievements, which contributed to the expansion of women's role in ecclesiastical life and in society in general. In the search for minutes, newspapers and periodicals from that period, we turned to the Public Library of Mato Grosso, the archives of the Presbyterian Church of Cuiabá and the Hemeroteca Nacional. We compliled fragments of the participation of some women in the Presbyterian Church of Cuiabá, in an attempt to remove them from invisibility. It is important to highlight that in the development of this research, especially in the citations, the language of each period was respected, in accordance with the rules of Portuguese language at the time.